Early Detection of risk of autism spectrum disorder based on recurrence quantification analysis of electroencephalographic signals - Pistorius, T; Aldrich, Chris; Auret, Lidia; Pineda, J (The Printing House, 2013)
Early detection of autism spectrum disorder (ASD) in infants is vital in maximizing the impact and potential long-term outcomes of early delivery of rehabilitative therapies. To date no definitive diagnostic test for ASD exists. Electroencephalography is a noninvasive method used to capture underlying electrical changes in brain activity. This proof-of-concept study suggests that recurrence quantification analysis features computed from resting state spontaneous eyes-closed electroencephalographic (EEG) signals may be useful biomarkers for early detection of risk of ASD.